2014
DOI: 10.12748/uujms.201416497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bark flour on the mechanical properties of HDPE composites

Abstract: The objective of this study was to evaluate the replacement of wood flour by Turkish pine bark residues for production of wood plastic composites. High density polyethylene was chosen as matrix and seven different compositions were used for production of composites. In order to compare the effect of bark residues flour as a filler, bark residues-HDPE composites were produced with various wt% bark residues loading (10, 20, 30 and 40 wt%). Bark residues filled HDPE pellets were produced by using a twin-screw ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Polymers used are either in virgin or recycled form. Currently, the main applications of WPC products are cladding, decking, fencing, paneling, and furniture (Çetin et al 2014;Özmen et al 2014;Çavuş and Mengeloğlu 2016;Martikka and Karki 2019;Mengeloğlu and Çavuş 2019). Good adhesion of matrix with WF improves the mechanical properties of WPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers used are either in virgin or recycled form. Currently, the main applications of WPC products are cladding, decking, fencing, paneling, and furniture (Çetin et al 2014;Özmen et al 2014;Çavuş and Mengeloğlu 2016;Martikka and Karki 2019;Mengeloğlu and Çavuş 2019). Good adhesion of matrix with WF improves the mechanical properties of WPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Pedieu et al [32] showed that 70% of wood fibers in the core layer of particleboard could be replaced by white birch inner bark while maintaining the required mechanical and physical properties. Another study by Cetin et al [33] showed that bark in the core layer significantly lowered the formaldehyde emissions of the particleboard. The positive effect of amount of bark used to replace technical flour was observed only in the case of specific concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…An opposite effect was obtained for HDPE matrix composites which showed significantly higher values for small particle. These results are borne out by two other studies: Yemele et al and Ç etina et al [18,38].…”
Section: Resultsmentioning
confidence: 52%